E-learning readiness among English language teachers in Sabah, Malaysia: A pilot study - Ke Hu; Asmaa AlSaqqaf; Suyansah Swanto (Journal of English Language Teaching Innovations and Materials (Jeltim), 2020)
This paper aims to assess the reliability of the instrument adapted to identify the level of e-learning readiness among English language teachers at secondary schools in Sabah, Malaysia. Five dimensions selected from Chapnick’s (2000) E-Learning Readiness Model (i.e., psychological readiness, technological skills readiness, equipment readiness, content readiness, and human resource readiness) were subjected for investigation. Using a simple random sampling, this quantitative research employed an online cross-sectional questionnaire to collect data from English language teachers at different secondary schools in Sabah. 72 English language teachers responded to the online questionnaire, where Cronbach’s alpha was used to test the reliability of the questionnaire items. Findings demonstrate that the overall Cronbach’s alpha of the survey reached 0.871. Further results show that the Cronbach’s alpha of the five dimensions ranges between 0.826 scored by Human Resource Readiness and 0.886 reported by Technological Skills Readiness. These findings show that the questionnaire is highly reliable to be used within the context of Sabah secondary schools. Limitations of the study and recommendations for further research are discussed.